Analysis of Hemp Seed Oil Production Methods: Directions for Management of the Niche Oils Production Process in Small-scale Production Facilities - Czwartkowski, Kamil (Analiza metod produkcji oleju z nasion konopi: Kierunki zarządzania procesem produkcji olejów niszowych w małych zakładach produkcyjnych, 2024)
Aim: The market share of edible oils such as flax seed oil, hemp seed oil, pumpkin seed oil, nut oils, and nigella oil is not considerable. Due to the small scale of production and the manufacturers' orientation toward a consumer niche, these oils are classified as niche oils. The purpose of this paper was to compare the cost of producing hemp seed oil (Cannabis sativa L.) using four production methods as an example, to compare the physicochemical properties of the oils produced, and to evaluate each of the production methods used. Methodology: In the study, a cost calculation was made for the start-up of the processing line for each of the selected production methods based on actual inputs. Laboratory tests were conducted on the basic physicochemical parameters of the obtained hemp oils (natural pigment content, fatty acid profile, free fatty acid content, and oxidative stability), and a SWOT analysis of the production methods was performed. Results: It was found that the production of niche oils by pressing is economically the most reasonable and favourable physicochemical parameter that characterises the oils obtained in this way. The SWOT analysis of the selected production methods indicated the legitimacy of each analysed method and demonstrated its risks. Implications and recommendations: The analyses presented in this work showed that niche oils should be obtained by pressing (preferably low-temperature) in small oil plants, but this is only appropriate for some raw materials. Originality/value: There is no legislation in the European Union on the production of niche oils, and it is necessary to set a conceptual framework in which such regulations could be created.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 3, s. 66-79
Keywords: niche oils; niche oil production methods; niche oil production costs; break-even point; SWOT analysis; oleje niszowe; metody produkcji olejów niszowych; koszty produkcji; próg rentowności; analiza SWOT